Anti-Inflammatory and Anti-Microbial Effects of Prosopis Africana Methanol Stem Back Extract - Aduwamai, Umaru Hauwa; Oluwatosin, Jegede Olosola; Malgwi, Jemimah Mohammed; Umaru, Kerenhappuch Isaac (Darul Yasin Al Sys, 2024)
The anti-inflammatory and anti-microbial effect of Prosopis Africana methanol stem bark extract was determined. Results of qualitative phytochemical screening revealed the presence of tannins, saponins, flavonoids, alkaloids, phenols, steroids and terpenoids. The quantitative analysis revealed the quantity of alkaloids (0.11%), tannins (1.92%), phenols (3.77%), flavonoids (0.77%), steroids (0.14%), terpenoids (0.21%) and saponins (4.01%). The anti-inflammatory effect of methanol stem-bark extract of Prosopis africana was assessed in male albino rats using paw immersion method. The anti-inflammatory effect produced by methanol stem-bark extract of Prosopis africana was found to be significant (p<0.05) at the dose of 200mg/kg, which was more effective than other concentrations at time interval of 0-90minutes. The antimicrobial activities of the methanol stem-bark extract of Prosopis africana produced the highest zone of inhibition (l7mm) on Pseudomonas aeruginosa and the lowest zone of inhibition (11mm) on Staphylococcus aureus. The minimum inhibitory concentration value of Prosopis Africana methanol stem-bark extract against E.coli, S. aureus and P. areuginosa was 2.5mg/ml each compared to K. pneumonia which was 5.5mg/ml. Results obtained indicate the antimicrobial effect of the methanol stem-bark extract of Prosopis Africana against K. pneumoniae was more effective than ampicillin. This work has further supported the basis for the use of the plant as anti-inflammatory agent in the treatment of various diseases associated with the microorganisms studied.